Business Process Re-engineering and ERP System Implementation in Design Company - Bimantara, Ranggashakti; Bayupati, I Putu Agung; Rusjayanthi, Ni Kadek Dwi (JITTER : Jurnal Ilmiah Teknologi dan Komputer; Vol 3 No 1 (2022): JITTER, Vol.3, No.1, April 2022, 2022)
Data and information integration has an essential role in a business that every business actor needs to compete in the digitalization era. CV. Triloka is a company in design and development services that are currently proliferating but does not yet have a capable and integrated system. The company's operational activities are still carried out manually without using an integrated system which causes a decrease in work performance due to inefficient. Based on these problems, improvements were made to business processes from analysis to implementation by utilizing the Odoo system to produce best practice business processes following Enterprise Resource Planning (ERP). The research results are in the form of analysis of existing business processes, new business processes, implementation of Odoo modules, and results of system implementation questionnaires